Unique microbial communities persist in individual cystic fibrosis patients throughout a clinical exacerbation - Price, Katherine E (BioMed Central, 2013)
BACKGROUND: Cystic fibrosis (CF) is caused by inherited mutations in the cystic fibrosis transmembrane conductance regulator gene and results in a lung environment that is highly conducive to polymicrobial infection. Over a lifetime, decreasing bacterial diversity and the presence of Pseudomonas aeruginosa in the lung are correlated with worsening lung disease. However, to date, no change in community diversity, overall microbial load or individual microbes has been shown to correlate with the onset of an acute exacerbation in CF patients. We followed 17 adult CF patients throughout the course of clinical exacerbation, treatment and recovery, using deep sequencing and quantitative PCR to characterize spontaneously expectorated sputum samples RESULTS: We identified approximately 170 bacterial genera, 12 of which accounted for over 90% of the total bacterial load across all patient samples. Genera abundant in any single patient sample tended to be detectable in most samples. We found that clinical stages could not be distinguished by absolute Pseudomonas aeruginosa load, absolute total bacterial load or the relative abundance of any individual genus detected, or community diversity. Instead, we found that the microbial structure of each patient’s sputum microbiome was distinct and resilient to exacerbation and antibiotic treatment. CONCLUSION: Consistent with previously reported sputum microbiome studies we found that total and relative abundance of genera at the population level were remarkably stable for individual patients regardless of clinical status. Patient-by-patient analysis of diversity and relative abundance of each individual genus revealed a complex microbial landscape and highlighted the difficulty of identifying a universal microbial signature of exacerbation. Overall, at the genus level, we find no evidence of a microbial signature of clinical stage.